Open Questions on Ion–Neutral Collisions and Coupling in the Lower Thermosphere–Ionosphere: Electrodynamics, Energetics and Dynamics - Theodoros E. Sarris; Stelios Tourgaidis; Dimitrios Baloukidis; Maxime Grandin; Astrid Maute; Robert F. Pfaff; Jeffrey Thayer; James Clemmons; Karl Laundal; Hanli Liu; Panagiotis Pirnaris; Noora Partamies; et al. (Surveys in Geophysics, 2026)
The Lower Thermosphere–Ionosphere (LTI) is the interface region between the Earth’s atmosphere and space. It is modulated by the energy and momentum deposition from the magnetosphere above and by the impacting waves from the lower atmosphere. The LTI region is defined by the co-existence and interaction of neutral and ionized species within the region’s electric and magnetic fields. This interplay results in unique and complex interactions between neutrals and plasmas, that are not fully understood and quantified to this date. In this paper we present an overview of some of the most important open questions related to ion/neutral coupling and the resulting collisional electrodynamics, collisional energetics and collisional dynamics processes. We outline the key reasons for addressing these questions, and highlight methodologies that can lead to their closure in the upcoming years.

Social and Ecological Context Shape Biological Invasions in Complex Landscapes - George L. W. Perry; James M. R. Brock; Cameron B. Guy; Casey Hamilton; Finnbar Lee; Dion L. Pou; Elizabeth Williams; Erica A. H. Smithwick (Current Landscape Ecology Reports, 2025)

Quantitative insights into the spatio‐temporal variation of Atlantic salmon ( Salmo salar ) biomass in a river catchment using eDNA metabarcoding - William Bernard Perry; Nigel Milner; Ifan Bryn Jâms; Mark de Bruyn; Steve J. Ormerod; Kristy Deiner; Holly M. Bik; Gary Carvalho; John Colbourne; Bernard Jack Cosby; Isabelle Durance; Simon Creer (Journal of Fish Biology, 2025)
Effective species conservation and management requires comprehensive biomonitoring, enhanced by combining traditional and newer methodologies, such as environmental DNA (eDNA) analyses. A seasonal pulse of spawning adult Atlantic salmon ( Salmo salar ) was detected by normalised eDNA 12S reads from metabarcoding, which facilitated estimation of spatial patterns in salmon biomass. A strong relationship was found between normalised reads in the lower section of the River Conwy (Wales, UK) and whole‐river adult biomass (estimated from rod catch data and a fish counter), explaining 61% of the variation in a linear regression. Moreover, the positive linear relationship between adult biomass and partial effect on normalised reads occurred after the biomass estimate exceeded 1500 kg, indicating a threshold where normalised reads become representative of biomass. The relationship observed between normalised reads and biomass, as well as the unique profiles of normalised reads at each of the sites, supports the hypothesis of limited eDNA transport among sampling sites that were 2–4 km apart. River pH showed a significant non‐linear relationship with normalised reads, with a peak in partial effect on normalised reads at pH 6.5. Partial effect on normalised reads also showed a positive linear relationship with flow (discharge), while also peaking at the highest average monthly air temperatures (14°C). These trends are contrary to what would be expected from eDNA decay, dilution or transport, demonstrating that metabarcoding is robust to such influences, reinforcing the interpretation of trends driven by Atlantic salmon ecology and physiology. For example, pH effects reflect beneficial conditions for eggs and perhaps habitat preference for spawners, flow effects reflect the annual return of salmon during higher flows which aid upstream migration, tributary entry and spawning, and, finally, temperature effects reflect higher metabolic rates and greater shedding of eDNA.

Estimating Spatially Explicit Survival and Mortality Risk From Telemetry Data With Thinned Point Process Models - Joseph M. Eisaguirre; Madeleine G. Lohman; Graham G. Frye; Heather E. Johnson; Thomas V. Riecke; Perry J. Williams (Ecology Letters, 2025)
Mortality risk for animals often varies spatially and can be linked to how animals use landscapes. While numerous studies collect telemetry data on animals, the focus is typically on the period when animals are alive, even though there is important information that could be gleaned about mortality risk. We introduce a thinned spatial point process (SPP) modelling framework that couples relative abundance and space use with a mortality process to formally treat the occurrence of mortality events across the landscape as a spatial process. We show how this model can be embedded in a hierarchical statistical framework and fit to telemetry data to make inferences about how spatial covariates drive both space use and mortality risk. We apply the method to two data sets to study the effects of roads and habitat on spatially explicit mortality risk: (1) VHF telemetry data collected for willow ptarmigan in Alaska, and (2) hourly GPS telemetry data collected for black bears in Colorado. These case studies demonstrate the applicability of this method for different species and data types, making it broadly useful in enabling inferences about the mechanisms influencing animal survival and spatial population processes while formally treating survival as a spatial process, especially as the development and implementation of joint analyses continue to progress.

Sustainable mining in tropical, biodiverse landscapes: Environmental challenges and opportunities in the archipelagic Philippines - Justine Perry T. Domingo; Gawen R.T. Jenkin; Laura Quick; Richard D. Williams; Karen A. Hudson-Edwards; Cecilia Tortajada; Patrick Byrne; Tom J. Coulthard; Jenielyn T. Padrones; Rich Crane; Cris Reven L. Gibaga; Grigorios Vasilopoulos; et al. (Journal of Cleaner Production, 2024)

Identifying priority sites for whale shark ship collision management globally - Freya C. Womersley; Christoph A. Rohner; Kátya Abrantes; Pedro Afonso; Shin Arunrugstichai; Steffen S. Bach; Shir Bar; Adi Barash; Peter Barnes; Adam Barnett; Ginevra Boldrocchi; Noemie Buffat; et al. (Science of The Total Environment, 2024)

Nutrient function over form: Organic and inorganic nitrogen additions have similar effects on lake phytoplankton nutrient limitation - Sabrina N. Volponi; Heather L. Wander; David C. Richardson; Clayton J. Williams; Denise A. Bruesewitz; Shelley Arnott; Jennifer A. Brentrup; Hailee L. Edwards; Holly A. Ewing; Kristen Holeck; Lauren Johnson; Brian S. Kim; et al. (Limnology and Oceanography, 2023)
The concentration of dissolved organic nitrogen (DON) is increasing in many northern hemisphere lakes, yet its use by phytoplankton and fate in the environment seldom have been quantified. We conducted 1 week, in situ, microcosm incubations across 25 lakes in northeastern North America to understand how DON, dissolved inorganic nitrogen (DIN), and dissolved inorganic phosphorus (P) affected phytoplankton biomass. In addition, we tested whether lakes were limited by single macronutrients (N or P) or colimited by both. Phytoplankton biomass in 80% of lakes responded similarly to DON and DIN additions. Of the lakes where N form produced differential responses, the majority of phytoplankton communities exhibited greater biomass accumulation with DON than DIN. Colimitation was the most common type of nutrient limitation among the study lakes, followed by P limitation. Limitation type shifted with N form in 40% of the study lakes, but without consistent patterns explaining how shifts occurred. Regardless of N form, lakes with watersheds more dominated by agriculture and higher total dissolved nitrogen (TDN) tended to show P‐limited phytoplankton responses, while lakes with less agricultural watersheds and lower TDN tended to show colimited phytoplankton responses. Finally, ambient TDN and total phosphorus (TP) nutrient concentrations were stronger predictors of limitation type than ambient TDN : TP ratios. The different contributions of DON and DIN to phytoplankton biomass in some of our study lakes suggest that DON loading from surrounding watersheds may be an overlooked component in predicting phytoplankton productivity and nutrient limitation dynamics in freshwater ecosystems.

Memantine treatment does not affect compulsive behavior or frontostriatal connectivity in an adolescent rat model for quinpirole-induced compulsive checking behavior - Milou Straathof; Erwin L. A. Blezer; Christel E. Smeele; Caroline van Heijningen; Annette van der Toorn; Jan K. Buitelaar; Jeffrey C. Glennon; Willem M. Otte; Rick M. Dijkhuizen; Jan Buitelaar; Saskia de Ruiter; Jilly Naaijen; et al. (Psychopharmacology, 2022)
Rationale Compulsivity often develops during childhood and is associated with elevated glutamate levels within the frontostriatal system. This suggests that anti-glutamatergic drugs, like memantine, may be an effective treatment. Objective Our goal was to characterize the acute and chronic effect of memantine treatment on compulsive behavior and frontostriatal network structure and function in an adolescent rat model of compulsivity. Methods Juvenile Sprague–Dawley rats received repeated quinpirole, resulting in compulsive checking behavior ( n = 32; compulsive) or saline injections ( n = 32; control). Eight compulsive and control rats received chronic memantine treatment, and eight compulsive and control rats received saline treatment for seven consecutive days between the 10th and 12th quinpirole/saline injection. Compulsive checking behavior was assessed, and structural and functional brain connectivity was measured with diffusion MRI and resting-state fMRI before and after treatment. The other rats received an acute single memantine (compulsive: n = 12; control: n = 12) or saline injection (compulsive: n = 4; control: n = 4) during pharmacological MRI after the 12th quinpirole/saline injection. An additional group of rats received a single memantine injection after a single quinpirole injection ( n = 8). Results Memantine treatment did not affect compulsive checking nor frontostriatal structural and functional connectivity in the quinpirole-induced adolescent rat model. While memantine activated the frontal cortex in control rats, no significant activation responses were measured after single or repeated quinpirole injections. Conclusions The lack of a memantine treatment effect in quinpirole-induced compulsive adolescent rats may be partly explained by the interaction between glutamatergic and dopaminergic receptors in the brain, which can be evaluated with functional MRI.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

The Effect of Marsh Age on Ecosystem Function in a Rapidly Transgressing Marsh - Amy K. Langston; Daniel J. Coleman; Nathalie W. Jung; Justin L. Shawler; Alexander J. Smith; Bethany L. Williams; Serina S. Wittyngham; Randolph M. Chambers; James E. Perry; Matthew L. Kirwan (Ecosystems, 2022)

Recursive Bayesian computation facilitates adaptive optimal design in ecological studies - Clinton B. Leach; Perry J. Williams; Joseph M. Eisaguirre; Jamie N. Womble; Michael R. Bower; Mevin B. Hooten (Ecology, 2022)
Optimal design procedures provide a framework to leverage the learning generated by ecological models to flexibly and efficiently deploy future monitoring efforts. At the same time, Bayesian hierarchical models have become widespread in ecology and offer a rich set of tools for ecological learning and inference. However, coupling these methods with an optimal design framework can become computationally intractable. Recursive Bayesian computation offers a way to substantially reduce this computational burden, making optimal design accessible for modern Bayesian ecological models. We demonstrate the application of so‐called prior‐proposal recursive Bayes to optimal design using a simulated data binary regression and the real‐world example of monitoring and modeling sea otters in Glacier Bay, Alaska. These examples highlight the computational gains offered by recursive Bayesian methods and the tighter fusion of monitoring and science that those computational gains enable.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Recycling of Nitrate and Organic Matter by Plants in the Vadose Zone of a Saturated Riparian Buffer - Patience Bosompemaa; Eric Wade Peterson; William Perry; Wondwosen M. Seyoum (Water, Air, & Soil Pollution, 2021)

Spatiotemporal Analysis of Water Quality Indicators in Small Lakes Using Sentinel-2 Satellite Data: Lake Bloomington and Evergreen Lake, Central Illinois, USA - Gare Ambrose-Igho; Wondwosen M. Seyoum; William L. Perry; Catherine M. O’Reilly (Environmental Processes, 2021)

Corrigendum: OceanGliders: A Component of the Integrated GOOS - Pierre Testor; Brad de Young; Daniel L. Rudnick; Scott Glenn; Daniel Hayes; Craig M. Lee; Charitha Pattiaratchi; Katherine Hill; Emma Heslop; Victor Turpin; Pekka Alenius; Carlos Barrera; et al. (Frontiers in Marine Science, 2021)

A review of a decade of lessons from one of the world’s largest MPAs: conservation gains and key challenges - Graeme C. Hays; Heather J. Koldewey; Samantha Andrzejaczek; Martin J. Attrill; Shanta Barley; Daniel T. I. Bayley; Cassandra E. Benkwitt; Barbara Block; Robert J. Schallert; Aaron B. Carlisle; Pete Carr; Taylor K. Chapple; et al. (Marine Biology, 2020)

OceanGliders: A Component of the Integrated GOOS - Pierre Testor; Brad de Young; Daniel L. Rudnick; Scott Glenn; Daniel Hayes; Craig M. Lee; Charitha Pattiaratchi; Katherine Hill; Emma Heslop; Victor Turpin; Pekka Alenius; Carlos Barrera; et al. (Frontiers in Marine Science, 2019)
The OceanGliders program started in 2016 to support active coordination and enhancement of global glider activity. OceanGliders contributes to the international efforts of the Global Ocean Observation System (GOOS) for Climate, Ocean Health, and Operational Services. It brings together marine scientists and engineers operating gliders around the world: (1) to observe the long-term physical, biogeochemical, and biological ocean processes and phenomena that are relevant for societal applications; and, (2) to contribute to the GOOS through real-time and delayed mode data dissemination. The OceanGliders program is distributed across national and regional observing systems and significantly contributes to integrated, multi-scale and multi-platform sampling strategies. OceanGliders shares best practices, requirements, and scientific knowledge needed for glider operations, data collection and analysis. It also monitors global glider activity and supports the dissemination of glider data through regional and global databases, in real-time and delayed modes, facilitating data access to the wider community. OceanGliders currently supports national, regional and global initiatives to maintain and expand the capabilities and application of gliders to meet key global challenges such as improved measurement of ocean boundary currents, water transformation and storm forecast.

The Second Warning to Humanity – Providing a Context for Wetland Management and Policy - C. M. Finlayson; Gillian T. Davies; William R. Moomaw; G. L. Chmura; Susan M. Natali; J. E. Perry; N. Roulet; Ariana E. Sutton-Grier (Wetlands, 2019)

Evaluation of a traditional Māori harvesting method for sampling kōura (freshwater crayfish, Paranephrops planifrons ) and toi toi (bully, Gobiomorphus spp.) populations in two New Zealand streams - Ian A. Kusabs; Brendan J. Hicks; John M. Quinn; William L. Perry; Hēmi Whaanga (New Zealand Journal of Marine and Freshwater Research, 2018)
Representative sampling of crayfish in streams is often impractical, especially in non‐wadable habitats, or in areas with soft substrates. Whakaweku are artificial habitats made from bracken fern ( Pteridium esculentum ) that can be used successfully in a range of habitats. We compared whakaweku, minnow traps, fyke nets and electrofishing for sampling freshwater crayfish (kōura; Paranephrops planifrons ) and bullies (toi toi; Gobiomorphus spp .) in two streams with differing stream characteristics and fish assemblages. Whakaweku captured a full‐size range of kōura of both sexes, including small kōura (OCL 7–12 mm) that were not caught by minnow traps or fyke nets. Colonisation by kōura reached 90% of maximum after 2 weeks and CPUE was constant from 2 to 9 weeks. After 9 weeks, CPUE decreased due to decay of the fern fronds. Whakaweku are an effective sampling tool that are inexpensive, simple to set, and do not require expensive equipment or specialised training.

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Wetlands In a Changing Climate: Science, Policy and Management - William R. Moomaw; G. L. Chmura; Gillian T. Davies; C. M. Finlayson; B. A. Middleton; Susan M. Natali; J. E. Perry; N. Roulet; Ariana E. Sutton-Grier (Wetlands, 2018)

Mother–infant interactions and regional brain volumes in infancy: an MRI study - Vaheshta Sethna; Inês Pote; Siying Wang; Maria Gudbrandsen; Anna Blasi; Caroline McCusker; Eileen Daly; Emily Perry; Kerrie P. H. Adams; Maria Kuklisova-Murgasova; Paula Busuulwa; Sarah Lloyd-Fox; et al. (Brain Structure and Function, 2017)

The basis function approach for modeling autocorrelation in ecological data - Trevor J. Hefley; Kristin M. Broms; Brian M. Brost; Frances E. Buderman; Shannon L. Kay; Henry R. Scharf; John R. Tipton; Perry J. Williams; Mevin B. Hooten (Ecology, 2017)
Analyzing ecological data often requires modeling the autocorrelation created by spatial and temporal processes. Many seemingly disparate statistical methods used to account for autocorrelation can be expressed as regression models that include basis functions. Basis functions also enable ecologists to modify a wide range of existing ecological models in order to account for autocorrelation, which can improve inference and predictive accuracy. Furthermore, understanding the properties of basis functions is essential for evaluating the fit of spatial or time‐series models, detecting a hidden form of collinearity, and analyzing large data sets. We present important concepts and properties related to basis functions and illustrate several tools and techniques ecologists can use when modeling autocorrelation in ecological data.

CTFS ‐Forest GEO : a worldwide network monitoring forests in an era of global change - Kristina J. Anderson‐Teixeira; Stuart J. Davies; Amy C. Bennett; Erika B. Gonzalez‐Akre; Helene C. Muller‐Landau; S. Joseph Wright; Kamariah Abu Salim; Angélica M. Almeyda Zambrano; Alfonso Alonso; Jennifer L. Baltzer; Yves Basset; Norman A. Bourg; et al. (Global Change Biology, 2015)
Global change is impacting forests worldwide, threatening biodiversity and ecosystem services including climate regulation. Understanding how forests respond is critical to forest conservation and climate protection. This review describes an international network of 59 long‐term forest dynamics research sites ( CTFS ‐Forest GEO ) useful for characterizing forest responses to global change. Within very large plots (median size 25 ha), all stems ≥1 cm diameter are identified to species, mapped, and regularly recensused according to standardized protocols. CTFS ‐Forest GEO spans 25°S–61°N latitude, is generally representative of the range of bioclimatic, edaphic, and topographic conditions experienced by forests worldwide, and is the only forest monitoring network that applies a standardized protocol to each of the world's major forest biomes. Supplementary standardized measurements at subsets of the sites provide additional information on plants, animals, and ecosystem and environmental variables. CTFS ‐Forest GEO sites are experiencing multifaceted anthropogenic global change pressures including warming (average 0.61 °C), changes in precipitation (up to ±30% change), atmospheric deposition of nitrogen and sulfur compounds (up to 3.8 g N m −2 yr −1 and 3.1 g S m −2 yr −1 ), and forest fragmentation in the surrounding landscape (up to 88% reduced tree cover within 5 km). The broad suite of measurements made at CTFS ‐Forest GEO sites makes it possible to investigate the complex ways in which global change is impacting forest dynamics. Ongoing research across the CTFS ‐Forest GEO network is yielding insights into how and why the forests are changing, and continued monitoring will provide vital contributions to understanding worldwide forest diversity and dynamics in an era of global change.

Capsaicin induces apoptosis in human small cell lung cancer via the TRPV6 receptor and the calpain pathway - Jamie K. Lau; Kathleen C. Brown; Aaron M. Dom; Theodore R. Witte; Brent A. Thornhill; Clayton M. Crabtree; Haley E. Perry; J. Michael Brown; John G. Ball; Rebecca G. Creel; C. Luke Damron; William D. Rollyson; et al. (Apoptosis, 2014)

Importance of Biogeomorphic and Spatial Properties in Assessing a Tidal Salt Marsh Vulnerability to Sea-level Rise - Karen M. Thorne; Deborah L. Elliott-Fisk; Glenn D. Wylie; William M. Perry; John Y. Takekawa (Estuaries and Coasts, 2014)

Effects of risperidone, amisulpride and nicotine on eye movement control and their modulation by schizotypy - Anne Schmechtig; Jane Lees; Lois Grayson; Kevin J. Craig; Rukiya Dadhiwala; Gerard R. Dawson; J. F. William Deakin; Colin T. Dourish; Ivan Koychev; Katrina McMullen; Ellen M. Migo; Charlotte Perry; et al. (Psychopharmacology, 2013)

Erratum to: Measuring sediment accretion in early tidal marsh restoration - John Y. Takekawa; Isa Woo; Nicole D. Athearn; Scott Demers; Rachel J. Gardiner; William M. Perry; Neil K. Ganju; Gregory G. Shellenbarger; David H. Schoellhamer (Wetlands Ecology and Management, 2010)

Measuring sediment accretion in early tidal marsh restoration - John Y. Takekawa; Isa Woo; Nicole D. Athearn; Scott Demers; Rachel J. Gardiner; William M. Perry; Neil K. Ganju; Gregory G. Shellenbarger; David H. Schoellhamer (Wetlands Ecology and Management, 2010)

Nicotine self-administration in the rat: effects of hypocretin antagonists and changes in hypocretin mRNA - Mark G. LeSage; Jennifer L. Perry; Catherine M. Kotz; David Shelley; William A. Corrigall (Psychopharmacology, 2010)

The Neuroscience Information Framework: A Data and Knowledge Environment for Neuroscience - Daniel Gardner; Huda Akil; Giorgio A. Ascoli; Douglas M. Bowden; William Bug; Duncan E. Donohue; David H. Goldberg; Bernice Grafstein; Jeffrey S. Grethe; Amarnath Gupta; Maryam Halavi; David N. Kennedy; et al. (Neuroinformatics, 2008)

Monoclonal antibodies reveal changes in predator efficiency with prey spatial pattern - GEORGIANNE J. K. GRIFFITHS; COLIN J. ALEXANDER; JOHN M. HOLLAND; PETER J. KENNEDY; JOE N. PERRY; WILLIAM O. C. SYMONDSON; LINTON WINDER (Molecular Ecology, 2008)
Spatially explicit predator–prey interactions can alter the predatory potential of natural enemies augmented through conservation biological control. To test hypotheses regarding such interactions and predatory efficiency, we used a combination of molecular techniques and mark–release–recapture to study the foraging behaviour of a generalist carabid predator, Poecilus cupreus , in response to spatial patterns of its cereal aphid prey ( Metapolophium dirhodum and Sitobion avenae ). Beetle and aphid numbers were measured across two grids of sampling locations, within which aphid spatial pattern had been manipulated to generate patchy and more homogenous distributions. Aphid consumption was measured by enzyme‐linked immunosorbent assays (ELISA) of beetle gut contents, using an aphid‐specific monoclonal antibody. Movement and distribution patterns suggest that P. cupreus does not aggregate at, nor instigate prey‐taxis within, aphid patches. However, more than two‐thirds of the 2169 P. cupreus tested by ELISA had consumed aphids and the proportion of beetles containing aphid proteins was positively related to aphid density. Against expectation, the proportion of predators feeding on aphids was greatest where prey were homogenously distributed, and this was attributed to the loss of partial refuges for prey in aphid patches. The functional value of this type of uniform foraging strategy is ideally suited to early colonization of the crop habitat, when aphid numbers are low, before populations build up and form strong spatial patterns.

Ecological and economic implications of a tropical jellyfish invader in the Gulf of Mexico - William M. Graham; Daniel L. Martin; Darryl L. Felder; Vernon L. Asper; Harriet M. Perry (Biological Invasions, 2003)

Implications of Hybridization between Introduced and Resident Orconectes Crayfishes - William L. Perry; Jeffrey L. Feder; David M. Lodge (Conservation Biology, 2001)
One of the most imperiled taxonomic groups in North American freshwaters is that of crayfish ( Decapoda: Astacoidea): over 30% of the 390 species are threatened or endangered. This situation is globally significant because 80% of the world's crayfish species are North American. Few studies have examined the environmental changes that most threaten crayfish biodiversity, but competition and hybridization with non‐native crayfishes appear to be among the most important threats to native crayfishes. The rusty crayfish, Orconectes rusticus , native to southwestern Ohio has been introduced widely throughout the United States and is displacing two resident taxa, O. propinquus and O. virilis , in northern Wisconsin. Using morphological and allozyme comparisons of crayfish from allopatric and sympatric populations, we tested whether O. rusticus is hybridizing with the resident crayfishes in northern Wisconsin. We found no evidence of hybridization between O. virilis and either O. rusticus or O. propinquus . In contrast, numerous morphologically intermediate crayfish between O. rusticus and O. propinquus occurred at sympatric sites, and many of these individuals possessed allozymes diagnostic for both species in allopatry. Over 6% of the crayfish at one sympatric site were putative F 1 hybrids, 4% were putative F 2 individuals ( hybrid × hybrid origin), and 13% were putative backcrosses ( product of hybrid × parental matings). This is the first genetic documentation of hybridization between a resident and invading crayfish. Our results suggest that genetic mechanisms play a role in the extirpation of O. propinquus by O. rusticus and are consistent with observations of other researchers suggesting that hybridization with non‐native species is common among crayfishes at many other locations. High rates of endemism and widespread introductions of non‐native crayfish suggest that invasions and hybridization are a major threat to crayfish biodiversity.

Impact of Regional Intestinal pH Modulation on Absorption of Peptide Drugs: Oral Absorption Studies of Salmon Calcitonin in Beagle Dogs - Yong-Hee Lee; Barbara A. Perry; Stacy Labruno; Hee Sang Lee; William Stern; Lisa M. Falzone; Patrick J. Sinko (Pharmaceutical Research, 1999)

Biopharmaceutical Approaches for Developing and Assessing Oral Peptide Delivery Strategies and Systems: In Vitro Permeability and In Vivo Oral Absorption of Salmon Calcitonin - Patrick J. Sinko; Yong-Hee Lee; Vijaya Makhey; Glen D. Leesman; John P. Sutyak; Hongshi Yu; Barbara Perry; Curtis L. Smith; Peidi Hu; Erik J. Wagner; Lisa M. Falzone; Laura T. McWhorter; et al. (Pharmaceutical Research, 1999)